Distribution of Salacca zalacca ‘Kelapa’ - Pudji Widodo; Wiwik Herawati; Sukarsa Sukarsa (Fakultas Biologi | Universitas Jenderal Soedirman, 2019)
Salak or snake fruit (Salacca zalacca) or salak is a kind of popular fruit originated from Sumatra and Java. There are many cultivars including both the wild and the hybrid ones. One of many cultivars namely S. zalacca ‘Kelapa’ was observed for their distribution. This cultivar is considered to be unusual because it has only a few spines on its petioles. This cultivar was previously found only in Karangasem Bali especially in the subdistrict of Sibetan, Selat, and Rendang and in Batujajar in West Java. A new record was found in Banjarnegara especially in Sokanandi Village. A map of the distribution of this cultivar is presented.